Morphological and anatomical aspects of birdsfoot trefoil and big trefoil - Maroso,Rita Poles (2009)
This study was carried out with the objective of describing the aerial and underground organs of birdsfoot trefoil [Lotus corniculatus (São Gabriel and ARS-2620 cultivars)] and big trefoil [Lotus uliginosus (Maku cultivar)]. The plants were cultivated in pots and harvested at 150 and 210 days after sowing. Stems, leaves and roots were prepared in according to conventional anatomical techniques. The anatomical structures of L. corniculatus and L. uliginosus differed in terms of pith cell integrity, starch content in the parenchyma root cell and underground stem cortex. The leaves were amphistomatic, with phenolic idioblasts, small vascular bundles and few conducting elements. The underground system was diffuse, with adventitious shoots that grew in two directions, had no cataphylls, emerged from the ground, and gave rise to aerial stems. The morphological characteristics of the shoot system of both species matched the recent descriptions of soboles.